Russian and foreign practice of artificial intelligence in banking and its significance for business processes - E. A. Zolotova; E. Yu. Kalashnikova; O. N. Chuvilova; S. M. Grishanov (Вестник Северо-Кавказского федерального университета, 2023)
The research is devoted to the study of the features and possibilities artificial intelligence in banking, substantiating its importance for the business processes of modern commercial banks. The Russian and foreign banking practice of using artificial intelligence, the volume of investments in the development of technology are considered. The assessment of the level of digitalization of the banking sector is given and the leading banks that are active users of artificial intelligence are identified. Particular attention is paid to the use of technology in the field of lending. The main problems of banks in assessing potential borrowers are identified. With this in mind, technological solutions have been developed aimed at improving the accuracy and efficiency of artificial intelligence when considering loan applications